Hepatic enzymes and immunoinflammatory response to Bio-C Temp bioceramic intracanal medication implanted into the subcutaneous tissue of rats - Lopes, Camila Soares [UNESP]; Delfino, Mateus Machado [UNESP]; Tanomaru-Filho, Mário [UNESP]; Sasso-Cerri, Estela [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Cerri, Paulo Sérgio [UNESP] (Springer Nature, 2022)
Our purpose was to evaluate the biocompatibility and hepatotoxicity of a new bioceramic intracanal medicament, Bio-C Temp (BIO). The biological properties of BIO were compared with calcium hydroxide-based intracanal medicament (Calen; CAL), used as gold pattern. Polyethylene tubes filled with BIO or CAL, and empty tubes (control group, CG) were implanted into subcutaneous tissue of rats. After 7, 15, 30 and 60 days, the samples were embedded in paraffin for morphological, quantitative and immunohistochemistry analyses. At 7 and 60 days, blood samples were collected for analysis of serum glutamic-oxaloacetic transaminase (GOT) and glutamic-pyruvic transaminase (GPT) levels. The data were submitted to two-way ANOVA and Tukey’s test (p ≤ 0.05). No significant difference was detected in serum GOT and GPT levels among BIO, CAL and CG specimens. In all periods, BIO specimens exhibited lower number of inflammatory cells and immunoexpression of IL-6, a pro-inflammatory cytokine, than CAL specimens. The reduction of these parameters was accompanied by significant increase in the collagen content and in the immunoexpression of IL-10, a cytokine involved in the tissue repair, over time. Our findings indicate that Bio-C Temp is biocompatible and had no hepatotoxicity effect.